PENGARUH KEPEMILIKAN INSTITUSIONAL TERHADAP KARAKTERISTIK PASAR SAHAM DI BURSA EFEK INDONESIA - Silalahi, Donalson (UNIKA Santo Thomas, 2016)
The role of institutional ownership in the financial markets became very important. However, until today there is no consensus among researchers about the influence of institutional ownership on the characteristic of stock market. Therefore, researchers are motivated to conduct further research the influence of institutional ownership on the characteristic of stock market. The research conducted at the Indonesian Stock Exchange with traded spread and adverse selection costs as dependent variable and institutional ownership as independent variable. In addition to institutional ownership, also used standard deviation of common stock price and trading volume as a control variable to clarify the relationship of institutional ownership on the characteristic of stock market. The study was conducted on 120 firms with observations in the period 2010-2011. All the required data obtained from the Indonesian Capital Market Directory. The results showed that: First, institutional ownership has a negative and significant effect on traded spread. Second, the variability of traded spread is able to be explained by the variability of institutional ownership, standard deviation of the stock price, and trading volume 24.8 percent. Third, institutional ownership has a negative and significant effect on adverse selection costs. Fourth, the variability of adverse selection costs is able to be explained by the variability of institutional ownership, standard deviation of the stock price, and trading volume 26.2 percent. Fifth, the relationship between institutional ownership to traded spread and adverse selection cost before and after entering the control variables remain negative and significant.